Budaya Hukum dan Pemberdayaan Masyarakat Pengusaha Batik Dalam Rangka Menanggulangi Limbah Batik di Kota Pekalongan - Ita Surayya (Jatiswara, 2016)
Environment and Development have strong correlation. The two of terms can be separable. In Pekalongan, rapid development of batik industry had increased serious pollution due to industries’ bad behaviour, which transfer batik waste to rivers without proper process based on AMDAL standard. UU No. 23 /1997 concerning Management of Environment provides equitable legal framework in supporting to industries to endeavour business activities with friendly environment. However, this thesis analyse that generally big hindrance in legal enforcement of environment lies at human behaviour, their commitment, and discipline to avoid and prevent pollution and environment destruction. The fracture society in social economic with low education level accumulates to lack of knowledge causes despairing society, which in turn to raise no conducive legal culture. The lack awareness in legal culture of society tends to receive any consequence of the bad quality of environment. This is because they believe that batik business is the only source of their life. They have no choose to find another job. Powerless of society is reflected to bad condition of socio-economic of society which reluctant and fracture to any change in their environment so that they loss their self-independence. Poor economic condition cause lack of fund to make installation of waste management. The low of socio-economic refers to poorness raise hopeless. Consequently, society just throw batik waste without proper process. Empowerment as awareness instrument is keyword to anticipate the problem. Improving legal knowledge of society through empowerment is highly necessary to improve positive legal awareness to prevent pollution. Government’s support to society empowerment becoming fundamental issue in analysing the legal culture. This is because through the empowerment, community will build their self-independence. It is important to strengthen societies values into societies involvement in managing natural resource based on legal justice. This program may allow society to have capacity in anticipating environment issues including batik waste problem that threats health and environment as main interest should be protected by law.